Patogenisitas beberapa isolat beauveria bassiana pada plutella xylostella pathogenicity of beauveria bassiana isolates On plutella xylostella - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Plutella xylostella (L.) (Lepidoptera : Plutellidae) is key pest on cabbage. P. xylostella can be infected by Beauveria bassiana from other insects. The objective of this study was to determine the pathogenicity five isolates of B. bassiana on P. xylostella. Those isolates were BbUjl (larvae of Lepidoptera), BbUj2 (rice brown planthopper), BbUj3 (rice brown planthopper), BbUj4 (rice seed bug), and BbUj5 (rice black bug). In the laboratorium every isolate was inoculated 5 pL spora suspension at rate 107 sporahnL to third instar P. xylostella larva used mikroliter syring. Each treatment used 10 larvae and was replicated five times. The pathogenicity of B. bassiana was determined based on mortality and LT, ,value. The potent isolate was tested to find LC50 subsequently tested on cabbage crop in the green house. The result of the study showed that BbUj1 from larvae of Lepidoptera was the potent isolate with LC50 of 9.49 x 105 spora/mL. LT50 was 2.67 days for the concentration 10' spora/mL. Green house application of B. bassiana at rate of 5 x 1012 spora/ha caused 57 percent mortality of P. xylostella larva seven days after treatment and LT50was 5.67 days. Key words : B. bassiana isolates, pathogenicity, P xylostella. INTISARI Plutella xylostella (L.) (Lepidoptera: Plutellidae) merupakan hama utama tanaman kubis. Jamur Beauveria bassiana dari serangga species lain diyakini mampu menginfeksi P. xylostella. Tujuan penelitian adalah untuk menentukan patogenisitas lima isolat B. bassiana pada: P. xylostella. isolat tersebut adalah BbUj 1 (inang larva Lepidoptera), BbUj2 (inang wereng, cokelat), BbUj3 (inane wereng cokelat), BbUj4 (inang walang sangit), dan BbUj5 (inang kepinaing tanah). Di laboratoriurn setiap isolat B. bassiana diinokulasikan pada instar tiga P. xylostella menggunakan mikroliter syringe sebanyak 5 pa, suspensi spora dengan kepekatan 107 spora/mL per ekor. Setiap perlakuan menggunakan 10 larva dan diulang a lima kali. Patogenisitas tertinggi di tentukan berdasarkan mortalitas dan nilai LT50, kemudian ditentukan nilai LC5onya. isolat yang paling patogenik diuji lebih lanjut pada tanaman kubis di bawah kondisi rumah kaca. Hasil kajian menunjukkan bahwa BbUj 1 berasal dari inang larva Lepidoptera merupakan isolat berpotensi dengan LC50 9,49 x 10' spora/mL. Pada konsentrasi 107 spora/mL, LT5 sebesar 2,67 hart. Aplikasi B. bassiana pada dosis 5 x 1012 spora/ha di rumah kaca rrtengakibatkan mortalitas larva P. xylostella pada hari ketujuh sebesar 57% dan LT50 5,67 hari. Kata kunci: B. bassiana, patogenisitas, P. xylostella